2013
DOI: 10.1080/2150704x.2013.842285
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of X-band SAR to wheat and barley leaf area index in the Merguellil Basin

Abstract: Remote sensing of vegetation by using active microwave sensors is important for the management of land and water resources. Microwave radiation at X-band penetrates only the upper part of the canopy; thus, radar backscattering comes mainly from the top vegetation layer, making the scattering from soil almost negligible. Fourteen in-situ measurement campaigns were carried out during which sixteen SAR images of COSMO-SkyMed and TerraSAR-X were acquired on the test site of Merguellil Basin, in the center of Tunis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Unfortunately, we obtained CSK images at VV polarization just in the first growth phase of wheat crops and therefore the decreasing trend was not confirmed at higher values of biomass for the presented data. Further investigations, carried out on a test site in Tunisia, on wheat fields well-developed confirmed instead this trend by using TerraSAR-X data too [Fontanelli et al, 2013]. An analogous behavior was observed on colza, which, at the beginning of its growth, is a plant with characteristics significantly different from those of wheat.…”
Section: Sensitivity To Vegetationmentioning
confidence: 63%
“…Unfortunately, we obtained CSK images at VV polarization just in the first growth phase of wheat crops and therefore the decreasing trend was not confirmed at higher values of biomass for the presented data. Further investigations, carried out on a test site in Tunisia, on wheat fields well-developed confirmed instead this trend by using TerraSAR-X data too [Fontanelli et al, 2013]. An analogous behavior was observed on colza, which, at the beginning of its growth, is a plant with characteristics significantly different from those of wheat.…”
Section: Sensitivity To Vegetationmentioning
confidence: 63%
“…[5]. Active and passive microwave remote-sensing techniques are thus an important source of data, for which numerous studies have proposed various inversion algorithms for soil and vegetation characterization, including operational estimations [6][7][8][9][10][11][12]. The Global Navigation Satellite System-Reflectometry (GNSS-R) is a microwave technique based on bistatic radar observations, which appeared at the beginning of the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increase in the vegetation contribution as a function of the LAI, combined with the decrease in the soil moisture contribution (Mv between 0.10 and 0.20 cm [87][88][89][90][91][92][93]. Previous results have shown that the radar signal decreases with an increase in the LAI for narrow leaf crops (wheat, alfalfa, and barley), and increases for board leaf crops (sunflower, corn, sorghum, and sugarcane) [91,93]. For example, Champion [87] studied the sensitivity of radar signals in C and X bands to the LAI of wheat crops (soil moisture values between 0.05 and 0.20 cm decreases as vegetation density increases (higher sensitivity for biomass lower than 1 kg/m 2 ).…”
mentioning
confidence: 99%